2004
DOI: 10.1111/j.1365-2141.2004.05233.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for simultaneous analysis of specific platelet antibodies: SASPA

Abstract: Anti-platelet antibodies cause several thrombocytopenic disorders such as autoimmune or alloimmune thrombocytopenia, post-transfusion purpura, drug-induced thrombocytopenia and refractoriness to platelet transfusion by eliminating platelets from the circulation. These antibodies can target specific platelet glycoproteins (GP), human leucocyte antigen (HLA) class I antigens or phospholipids (Kurata et al, 1993;Alcorta et al, 1996;Macchi et al, 1996Macchi et al, , 1997Cuadrado et al, 1997;Panzer et al, 1997;Kief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…Moreover, the multiple antibody detection by SASPA reduced working time to perform the assay. In a comparative investigation of SASPA and MAIPA, both direct and indirect, we demonstrated the same specificity for both methods [15]. Half of the patients with platelet-associated IgG (PAIgG) determined by PIFT remained negative in the GP-specific assays focusing on GP Ia/IIa, Ib/IX, IIb/IIIa as performed to date by MAIPA [14,16].…”
Section: Principles and Benefits Of The Saspa Methodsmentioning
confidence: 95%
See 3 more Smart Citations
“…Moreover, the multiple antibody detection by SASPA reduced working time to perform the assay. In a comparative investigation of SASPA and MAIPA, both direct and indirect, we demonstrated the same specificity for both methods [15]. Half of the patients with platelet-associated IgG (PAIgG) determined by PIFT remained negative in the GP-specific assays focusing on GP Ia/IIa, Ib/IX, IIb/IIIa as performed to date by MAIPA [14,16].…”
Section: Principles and Benefits Of The Saspa Methodsmentioning
confidence: 95%
“…In addition, sensitivity of the SASPA assay was at least similar or even higher compared to the MAIPA assay. Studies on the stability of SASPA results showed lower coefficients of variation compared to MAIPA results, indicating that SASPA is more robust [15].…”
Section: Principles and Benefits Of The Saspa Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant progress has also been achieved in the diagnostic field of platelet immunology. The recent introduction of the simultaneous analysis of specific platelet antibodies (SASPA) assay [12] and of recombinant platelet antigens [13] represent the most important developments. Such methods may contribute to gain knowledge about the heterogeneity of plateletspecific antigens and antibodies which represents a significant problem in the clinical diagnosis of immunologically mediated platelet disorders.…”
mentioning
confidence: 99%